Increased Carbon Partitioning to Secondary Metabolites Under Phosphorus Deficiency in Glycyrrhiza uralensis Fisch. Is Modulated by Plant Growth Stage and Arbuscular Mycorrhizal Symbiosis - Xie, Wei; Hodge, Angela; Hao, Zhipeng; Fu, Wei; Guo, Lanping; Zhang, Xin; Chen, Baodong (Frontiers in Plant Science, 2022)
Phosphorus (P) is one of the macronutrients limiting plant growth. Plants regulate carbon (C) allocation and partitioning to cope with P deficiency, while such strategy could potentially be influenced by plant growth stage and arbuscular mycorrhizal (AM) symbiosis. In a greenhouse pot experiment using licorice (Glycyrrhiza uralensis) as the host plant, we investigated C allocation belowground and partitioning in roots of P-limited plants in comparison with P-sufficient plants under different mycorrhization status in two plant growth stages. The experimental results indicated that increased C allocation belowground by P limitation was observed only in non-AM plants in the early growth stage. Although root C partitioning to secondary metabolites (SMs) in the non-AM plants was increased by P limitation as expected, trade-off patterns were different between the two growth stages, with C partitioning to SMs at the expense of non-structural carbohydrates (NSCs) in the early growth stage but at the expense of root growth in the late growth stage. These changes, however, largely disappeared because of AM symbiosis, where more root C was partitioned to root growth and AM fungus without any changes in C allocation belowground and partitioning to SMs under P limitations. The results highlighted that besides assisting with plant P acquisition, AM symbiosis may alter plant C allocation and partitioning to improve plant tolerance to P deficiency.